Google Sites Media with High Validity and Student Engagement in Learning: Media Google Sites dengan Validitas Tinggi dan Keterlibatan Siswa dalam Pembelajaran - Gessa, Andre Oklanda; Martha, Alfroki; Hendrizal (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid development of information and communication technology has transformed various sectors, including education. Specific Background: Despite this advancement, elementary education in Indonesia still heavily relies on conventional methods, as observed at SDN 27 Tapian Kandis where teachers primarily use printed materials. Knowledge Gap: Teachers face limitations in utilizing digital learning platforms due to a lack of understanding and training. Aims: This study aims to develop and evaluate a Google Sites-based learning medium on ecosystem material to enhance fifth-grade students’ interest in learning. Results: The media demonstrated high validity (92.95%), practicality (96%), and effectiveness (84.82%). The N-Gain score (0.8483) and student interest response (95%) indicate significant improvement in engagement and learning outcomes. Novelty: The developed Google Sites media integrates diverse features such as instructional videos, LKPD, quizzes, and teacher profiles—allowing for interactive, accessible, and visually rich content without requiring programming skills. Implications: This innovation proves that Google Sites can serve as an effective, practical, and scalable digital solution for enhancing student engagement and modernizing instructional practices in elementary education.Highlight : The study developed Google Sites-based media shown to be highly valid, practical, and effective in increasing 5th graders' learning interest. It used the ADDIE development model to systematically analyze, design, implement, and evaluate digital learning tools. Google Sites enabled interactive, multimedia-rich content tailored to Gen Z students, promoting motivation and digital literacy. Keywords : Learning Media, Google Sites, Student Engagement, Elementary Education, Digital Innovation